The population genetics of the Mute Swan Cygnus olor in Ireland - O’Donoghue, Paul D; O’Halloran, John; Bacon, Philip J; Smiddy, Patrick; Cross, Thomas F (Wildfowl, 1992)
Mute Swan population genetics were investigated from four localities throughout Ireland using protein electrophoresis. The products of ten presumptive loci were assayed in red blood cells and one in blood plasma. All but the latter (plasma esterase) were monomorphic. Allele frequencies at the EST locus did not differ significantly from previously published values from England and Scotland nor was there a significant spatial or temporal heterogeneity apparent within Ireland. These results do not support the hypothesis of reproductive isolation of Irish swan populations from England and Scotland or within Ireland. The previously recorded presence of limited variability in the English and Scottish Mute Swan populations at one locus (Lactate dehydrogenase) compared to those assayed in Ireland (where it was monomorphic) may mean that introduction(s) involved a limited number of individuals.